Makna Tradisi “ Pemacakhan “ pada Upacara Pernikahan Masyarakat Lampung Adat Saibatin Pekon Way Kerap, Kecamatan Semaka, Kabupaten Tanggamus, Lampung: Pendekatan Etnografi Komunikasi - Reni Susanti (Jurnal Studi Ilmu Sosial dan Politik, 2022)
Purpose: "Pemacakhan" is a habit carried out by the people of Lampung Saibatine specially the Kepaksian  Semaka community during the wedding ceremony procession, this tradition is a form of appreciation for the Traditional Head, skipper and extended family to the bride and groom and also pray for the good of their household and share in the happiness of the marriage. Research Methodology: In this study, researchers used qualitative research methods and used ethnographic communication research analysis. By using this method, researchers can provide an overview, explain, and associate each category with the data found. Result: Components of communication contained in the tradition" pemacakahan ", communication that takes place is more non-verbal communication. This non-verbal communication is contained in the tools and materials used in the procession of "Pemacakhan". The equipment and materials used in this procession are henna leaves, yellow rice, water mixed with talcum powder and banana leaves. All the equipment and materials used have good meaning and philosophy for the lives of the bride and groom, namely containing a prayer and hope for the extended family for their second household. Contribution: This research is expected to provide benefits for the development of communication science, especially in the ethnographic theory of communication, and can provide understanding to the public about the meaning of carrying out processionspemacakahan Lampung Saibatin tradition. Limitations: Data collection techniques used to obtain data in this study were interviews and documentation.